KEBERADAAN ANAK PUSAKO DALAM NOVEL WARISAN KARYA CHAIRUL HARUN: SUATU KAJIAN SOSIOLOGIS - Zulfardi D (JURNAL PENDIDIKAN ROKANIA, 2021)
This research aims to describe the existence of anak pusako using the sociological approach contained in the novel Warisan by Chairul Harun. This type of research is qualitatively descriptive with content analysis techniques. The problems analyzed are those related to the presence of anak pusako are (1) suffering, (2) responsibility, (3) affection. The results of this study illustrate that the suffering experienced by Anak Pusako in the Rumah Bako is caused by differences in the views of the Bako towards Anak Pusako. Anak Pusako who have a good attitude of responsibility will be loved by the Bako. The responsibility and affection of the Bako is influenced by the customary rules that apply in Minangkabau.